EFEKTIVITAS PEMBELAJARAN - Asmadawati, Asmadawati (AIN Padangsidimpuan, 2014)
AbstractThe effectiveness of teaching and learning is based on the principles, procedures and designs in order to achieve behavior change goals. In a study conducted is not a stray from the planned objectives. In other words, to direct the learning activities that are in place in accordance with the programs and objectives that has been planned. This is consistent with the meaning of the effectiveness of the proposed by Hasan Shadly that